2021
DOI: 10.2147/pgpm.s305780
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insomnia and Migraine Risk: A Case–Control and Bidirectional Mendelian Randomization Study

Abstract: Background The causal relationship between insomnia and migraine is contradictory and no study has been carried out among the Chinese population to date. Methods In this case, we conducted a case–control study and a bidirectional mendelian randomization (MR) analysis to determine whether insomnia is causally related to the development of migraine. The instrumental variables for insomnia were derived from the largest genome-wide association study of 1,331,010 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…There is genetic overlap between several sleep traits and migraine. 51 Moreover, insomnia is a risk factor for the development of migraine, 52,53 raising the question whether the circadian features of insomnia genes 54 are also relevant in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…There is genetic overlap between several sleep traits and migraine. 51 Moreover, insomnia is a risk factor for the development of migraine, 52,53 raising the question whether the circadian features of insomnia genes 54 are also relevant in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that not all epidemiological link can be confirmed by MR study. A case in point is that most epidemiological data believed that there is a bidirectional causal relationship between insomnia and migraine, only a one-way link has been established by MR study, namely that genetically predicted insomnia is the risk for migraine [36]. In future studies, the causal associations between allergic disease, asthma, and insomnia need to be further explored by MR studies with larger GWAS samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liability to migraine leads to an increased coronary artery disease risk (99). Third, two studies explored the relationship with sleep-related comorbidities and provided evidence for a significant causal effect of difficulty awakening (OR [95% CI] = 1.37 [1.12–1.68], P = 0.002) (81) and insomnia (OR [95% CI] = 1.24 [1.11–1.38], P = 1.01 × 10 −4 ) (100) on the risk of migraine. Fourth, various MRs exploring behavioural traits, such as smoking, alcohol and coffee consumption, have shown that a higher alcohol or coffee consumption leads to a reduced migraine risk (101).…”
Section: Causality In Migrainementioning
confidence: 99%